2021
DOI: 10.4266/acc.2020.00626
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of the patient transition process from the intensive care unit: a qualitative study

Abstract: Background:The transition of patients from the intensive care unit (ICU) to the general ward is challenging. Patients and caregivers experience high levels of anxiety during the transition period.This study aimed to explain the challenges that patients face during the transition process. Methods:In this qualitative research of conventional content analysis, data collection was conducted between February 2018 and July 2019 in educational hospitals affiliated with the Iran University of Medical Sciences. After o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
11
0
2
Order By: Relevance
“…Similar to the caregivers situating with other types of ICU, participants reported that their care efficiency of family members during the process of ICU transition was more affected by the internal and external environment, such as varied degrees of mental burdens and mixed emotional response, which led to their inactive, and even negative care activities (de Grood et al, 2018; Herling et al, 2020). These findings are consistent with reported experiences of participants who were in a state of care shock and sometimes disturbed during ICU transition (Ghorbanzadeh et al, 2021). During the transition period of ICU, professionals should provide psychological support, pay close attention to the real feelings of nurses, and dynamically assess their psychological status when evaluating their mental, emotional and cognitive status.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the caregivers situating with other types of ICU, participants reported that their care efficiency of family members during the process of ICU transition was more affected by the internal and external environment, such as varied degrees of mental burdens and mixed emotional response, which led to their inactive, and even negative care activities (de Grood et al, 2018; Herling et al, 2020). These findings are consistent with reported experiences of participants who were in a state of care shock and sometimes disturbed during ICU transition (Ghorbanzadeh et al, 2021). During the transition period of ICU, professionals should provide psychological support, pay close attention to the real feelings of nurses, and dynamically assess their psychological status when evaluating their mental, emotional and cognitive status.…”
Section: Discussionsupporting
confidence: 92%
“…Of the patients transferred to the ward, 90% received ward-based dietitian-prescribed individualized nutrition interventions. Continuity of nutritional interventions can be problematic during the transition from ICU to the ward [ 18 ]. Structured dietetic handover between ICU and ward dietitians to improve the transfer of nutritional history and meet nutritional needs for recovery were used [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transition process can be improved by obtaining knowledge about the challenges related to hospitalization and care in the ICU, as well as the organization of an environment and learning conditions (23) , as the preparation of the patient and his/her family needs to be expanded considering their individual needs (19)(20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%